2017
DOI: 10.4049/jimmunol.1600420
|View full text |Cite
|
Sign up to set email alerts
|

The Syk–NFAT–IL-2 Pathway in Dendritic Cells Is Required for Optimal Sterile Immunity Elicited by Alum Adjuvants

Abstract: Despite a long history and extensive usage of insoluble aluminum salts (alum) as vaccine adjuvants, the molecular mechanisms underpinning Ag-specific immunity upon vaccination remain unclear. Dendritic cells (DCs) are crucial initiators of immune responses, but little is known about the molecular pathways used by DCs to sense alum and, in turn, activate T and B cells. In this article, we show that alum adjuvanticity requires IL-2 specifically released by DCs, even when T cell secretion of IL-2 is intact. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
4
17
0
Order By: Relevance
“…In contrast to IL-2, we detected no differences in the expression of immunomodulatory molecules, such as TGF-β or indoleamine-2,3-dioxygenase 1, in CD83-deficient DCs after stimulation with TLR-Ls or LPS, respectively (Supplemental Figure 2F). In T cells, IL-2 expression is controlled by the transcription factor Nfatc2, and this pathway is described in DCs as an important route for T cell stimulation (32). Thus, we were interested in whether Nfatc2 signaling in BDMCs was modified in CD83 ΔDC in comparison with control animals.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to IL-2, we detected no differences in the expression of immunomodulatory molecules, such as TGF-β or indoleamine-2,3-dioxygenase 1, in CD83-deficient DCs after stimulation with TLR-Ls or LPS, respectively (Supplemental Figure 2F). In T cells, IL-2 expression is controlled by the transcription factor Nfatc2, and this pathway is described in DCs as an important route for T cell stimulation (32). Thus, we were interested in whether Nfatc2 signaling in BDMCs was modified in CD83 ΔDC in comparison with control animals.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of IL-2 expression specifically in dendritic cells reduced the antibody response to aluminum-adjuvanted vaccines. 123 However, the mouse immunization experiments in this report were carried out with Imject TM Alum, and the role of NFAT and DC-secreted IL-2 in the immune response to vaccines formulated with AH and AP adjuvants remains to be determined.…”
Section: Mechanism Of Action Of Aluminum Adjuvantsmentioning
confidence: 99%
“… 112) Flow cytometric analysis on tumor infiltrating lymphocytes showed that, in patients with GBM, the expression of immune checkpoint molecules like PD-1 and CTLA-4 were significantly higher than that in T-cells from peripheral blood mononuclear cells (PBMCs). 113) Glioma cells evade immune surveillance by expressing PD-1, CTLA-4, and other immune checkpoint molecules that negatively regulate cytotoxic T-lymphocytes (CTL) 114 , 115) (109, 110) and activate regulatory T-cells (Treg), which suppresses effector T-cells. 112) Collectively, PD-1/PD-L1 inhibitors and CTLA-4 inhibitors, called immune checkpoint inhibitors, have been developed for several cancers, including GBMs.…”
Section: Strategy For Enhancing Tmz Effectmentioning
confidence: 99%